Peace child - Richardson, Don, 1935-2018.; Richardson, Carol; Gospel Communications International, Inc. (Muskegon, MI : Gospel Communications International, 2000)
The true story of Christian missionaries Don and Carol Richardson and their work among the Sawi people of New Guinea.
Based on the book Peace Child by Don Richardson.
"This film contains some brief nudity in the native fashion."--Container.
This DVD contains the following languages: Arabic, Cebuano, English, French, German, Ilocano, Indonesian, Italian, Japanese, Korean, Mandarin, Polish, Russian, Spanish, Tagalog, Taiwanese, Zulu.
DVD player required.
Keywords: Missions -- Indonesia; Sawi (Indonesian people) -- Missions; Sawi (Indonesian people); New Guinea